(3GdMGhj aj GdWHs - (3CHhHcQ GdQGRj , eMeO Hf RcQjG, CHh HcQ GdQGRj,J (B311 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI GdebGdI GdQGHYI ef GdCYVGA GdCdeI s
(3BNQgG (B:s
(3aj YdGL GdQLGd jSbj GdHGfL MJj jNQL Jdc GdaVhd GdQOjFI Ke GdWYGe GdOSe Je GdLRA GdKGdK s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3JQcjG s
Keywords: (3eJaQbGJs